Diagnostic and prognostic biomarkers in autoimmune hepatitis-associated cirrhosis: insights into TBil, CD38, IL-22, TSP-1, GAL-3, and Cyc-C - Jiani Shi; Jingbo Fu; Caijie He; Jun Shen (Frontiers in Medicine)
BackgroundAutoimmune hepatitis (AIH) is a chronic inflammatory disease that can progress to cirrhosis and liver failure. While various biomarkers have been associated with AIH progression and prognosis, their specific roles in diagnosing, predicting, and managing cirrhosis, particularly in compensated cirrhosis, remain unclear. Accurately predicting 2-year survival and clinical outcomes for patients with compensated cirrhosis is a critical challenge.MethodsThis study analyzed clinical data from non-cirrhotic and cirrhotic AIH patients to identify factors influencing cirrhosis development and prognosis. Serum and nutritional indices were compared between groups with differing prognoses. The diagnostic efficacy of TSP-1, Gal-3, Cys-C, AIb, and PA was evaluated in compensated cirrhosis patients, and their prognostic value was validated using linear regression and Cox proportional hazards models.ResultsNo significant differences in gender, age, BMI, hypertension, diabetes history, or AMA positivity were observed between the non-cirrhotic AIH and cirrhotic AIH groups. However, TBil levels were significantly higher, and CD38 and IL-22 levels were significantly lower in the cirrhosis group. Multivariate logistic regression identified elevated TBil and reduced CD38 and IL-22 levels were associated with increased cirrhosis risk. Prognosis analysis revealed that patients with good outcomes had significantly lower TSP-1, Gal-3, and Cys-C levels and higher AIb and PA levels than those with poor outcomes. Cox proportional hazards modeling identified TSP-1, Gal-3, and Cys-C as independent risk factors and AIb and PA as protective factors influencing 2-year survival.ConclusionThis study underscores the critical roles of TBil, CD38, and IL-22 in cirrhosis development among AIH patients and validates the diagnostic and prognostic significance of TSP-1, Gal-3, Cys-C, AIb, and PA in compensated cirrhosis. These biomarkers facilitate early risk identification and inform clinical decision-making, contributing to improved management and outcomes for AIH patients.